Impact of intermittent hypoxia on long-term facilitation of minute ventilation and heart rate variability in men and women: do sex differences exist? - Wadhwa, Harpreet (2008)
Following exposure to intermittent hypoxia, respiratory motor activity and sympathetic nervous system activity may persist above baseline levels for over an hour. The present investigation was designed to determine whether sustained increases in minute ventilation and sympathovagal (S/V) balance, in addition to sustained depression of parasympathetic nervous system activity (PNSA), were greater in men compared with women following exposure to intermittent hypoxia. Fifteen healthy men and women matched for age, race, and body mass index were exposed to eight 4-min episodes of hypoxia during sustained hypercapnia followed by a 15-min end-recovery period. The magnitude of the increase in minute ventilation during the end-recovery period, compared with baseline, was similar in men and women (men, 1.52 ± 0.03; women, 1.57 ± 0.02 fraction of baseline; P < 0.0001). In contrast, depression of PNSA and increases in S/V balance were evident during the end-recovery period, compared with baseline, in men (PNSA, 0.66 ± 0.06 fraction of baseline, P < 0.0001; S/V balance, 2.8 ± 0.7 fraction of baseline, P < 0.03) but not in women (PNSA, 1.27 ± 0.19 fraction of baseline, P = 0.3; S/V balance, 1.8 ± 0.6 fraction of baseline, P = 0.2). We conclude that a sustained increase in minute ventilation, which is indicative of long-term facilitation, is evident in both men and women following exposure to intermittent hypoxia and that this response is independent of sex. In contrast, sustained alterations in autonomic nervous system activity were evident in men but not in women.